Sierra Leone series: the Pikin-to-Pikin Movement and its focus on child protection, education, nutrition and health. - Tahi (EdTech Hub, 2021)
Over the past few months, the EdTech Hub team has analysed and mapped the EdTech research landscape in Sierra Leone. In doing so, we have met a number of individuals and organisations that are exploring if and how technology can support the country’s education sector.   In week one, we connected with Abdulai Swaray and Bai Kamara from the Pikin-to-Pikin Movement.…
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Consultants needed for UNESCO ACCRA's review of ICT in Education Policy in Ghana - Tahi (EdTech Hub, 2021)
ICT Transforming Education in Africa: Review of ICT in Education Policy in Ghana  TERMS OF REFERENCE (TOR) FOR INDIVIDUAL CONSULTANTS 1. Background/Context  UNESCO Korean Funds-In-Trust ICT Transforming Education in Africa is a project developed under  the UNESCO-Korea Funds-in-Trust framework to support a selected number of Sub-Saharan  African countries to test scalable and effective models of using information and  communication technologies…
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH